2021
DOI: 10.1017/s095442242100007x
|View full text |Cite
|
Sign up to set email alerts
|

The potential nutrition-, physical- and health-related benefits of cow’s milk for primary-school-aged children

Abstract: Cow’s milk is a naturally nutrient-dense foodstuff. A significant source of many essential nutrients, its inclusion as a component of a healthy balanced diet has been long recommended. Beyond milk’s nutritional value, an increasing body of evidence illustrates cow’s milk may confer numerous benefits related to health. Evidence from adult populations suggests that cow’s milk may have a role in overall dietary quality, appetite control, hydration and cognitive function. Although evidence is limited compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 137 publications
(230 reference statements)
0
10
0
2
Order By: Relevance
“…Fat and protein in milk have the characteristics of easy digestion and absorption, especially for children and the elderly, so the content and proportion of fat and protein in milk is of great significance. Studies have shown that drinking milk can reduce the incidence of dental caries (Rumbold et al, 2021), cardiovascular disease (Soedamah-Muthu and de Goede 2018), metabolic syndrome (Crichton et al, 2011) and obesity (Abargouei et al, 2012). Dairy cattle breeding is essential for the development of the dairy industry and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Fat and protein in milk have the characteristics of easy digestion and absorption, especially for children and the elderly, so the content and proportion of fat and protein in milk is of great significance. Studies have shown that drinking milk can reduce the incidence of dental caries (Rumbold et al, 2021), cardiovascular disease (Soedamah-Muthu and de Goede 2018), metabolic syndrome (Crichton et al, 2011) and obesity (Abargouei et al, 2012). Dairy cattle breeding is essential for the development of the dairy industry and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Milk is considered as the only foodstuff that contains all different substances that are known to be essential for an adequate human nutrition (Davoodi et al 2013;Scholz-Ahrens et al 2020;Lin et al 2021). Therefore, the consumption of milk and milk products is usually recommended for a healthy and balanced human diet (Pereira 2014;Rumbold et al 2022). Regarding the health benefits, a number of epidemiological studies have shown the importance of consuming milk and dairy products (low-fat and fermented) in preventing various potential adverse health effects such as bone problems and osteoporosis (Rozenberg et al 2016;Fardellone et al 2017;Fardellone 2019;Ratajczak et al 2021), risk of childhood obesity (Thorning et al 2016) and type 2 diabetes mellitus (Alvarez-Bueno et al 2019;Awwad et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the consumption of milk and milk products is usually recommended for a healthy and balanced human diet (Pereira 2014; Rumbold et al . 2022). Regarding the health benefits, a number of epidemiological studies have shown the importance of consuming milk and dairy products (low‐fat and fermented) in preventing various potential adverse health effects such as bone problems and osteoporosis (Rozenberg et al .…”
Section: Introductionmentioning
confidence: 99%
“…Milk is a fresh liquid, clean, and normal mammary secretion produced by mammals for the nourishment of their young ones (Erickson et al, 2020). It is obtained by milking the udder of a properly fed and well-kept dairy animal (Rumbold et al, 2021). Milk is highly nutritious with micronutrients, macronutrients, and immunoglobulins that make an important part of the diet (Haug et al, 2007;Rani and Maheshwari, 2012;Penhaligan, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Milk is highly nutritious with micronutrients, macronutrients, and immunoglobulins that make an important part of the diet (Haug et al, 2007;Rani and Maheshwari, 2012;Penhaligan, et al, 2022). Milk from dairy animals (cattle, sheep, and goats) are an important food item for over 6 billion people all over the globe, and a major contributor to food security as it alleviates poverty and mitigates malnutrition (Rumbold et al, 2021). Despite the outstanding nutritional quality and health benefits of milk, it serves also as an excellent vehicle for the transmission of milkborne pathogens, which may cause serious health risks to consumers (Berhe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%